ТРАНСНАЦИОНАЛИЗАЦИЯ БИЗНЕСА КАК ФОРМА МОНОПОЛЬНОГО КОНТРОЛЯ В УСЛОВИЯХ ГЛОБАЛИЗАЦИИ МИРОВОЙ ЭКОНОМИКИ - Азатбек, Толкын (Journal of Economic Research & Business Administration, 2015)
Article is devoted disclosing of specific features of transnational corporations as odds of monopolization of economy. Motives of development of the multinational corporation in economy of Kazakhstan reveal. The analysis of advantages and lacks of activity of the multinational corporation of national economy is carried out.